Intonation Patterns of Madurese in Probolinggo Regency, Indonesia - Khoiriyah, Luluk; Wafa, Ali; Andayani, Sri (Journey: Journal of English Language and Pedagogy, 2026)
Intonation plays an important role in distinguishing sentence types and signaling grammatical meaning, yet its realization differs across languages. Although prosodic research on Austronesian languages has expanded in recent years, the intonation systems of many Indonesian regional languages remain insufficiently documented, including Madurese. This study investigates the distribution of pitch accents and boundary tones in the kasar register of Madurese spoken in the Pendalungan region of East Java. The analysis focuses on three sentence types: declaratives, yes–no questions, and wh-questions, derived from spontaneous talks between two native female speakers, acoustically analysed with Praat. Speech data were collected from spontaneous conversations between two female native speakers and analyzed acoustically using Praat. The results reveal seven pitch accent types and four boundary tones. Declarative utterances display the widest prosodic diversity, whereas yes–no questions consistently end in a low-falling (L–L%) boundary tone, unlike the rising intonation frequently associated with polar questions in several languages. Wh-questions exhibit prosodic characteristics that largely overlap with those of declaratives. These findings broaden the empirical description of Madurese intonation and provide evidence that the relationship between sentence type and intonation is shaped by language-specific prosodic conventions. More importantly, the consistent realization of yes–no interrogatives with a low-falling boundary tone challenges widely held cross-linguistic assumptions about interrogative intonation and offers new evidence that Austronesian prosodic systems may be typologically more diverse than previously considered.